Assessing size-dependent cytotoxicity of boron nitride nanotubes using a novel cardiomyocyte AFM assay. Issue 5 (29th March 2019) - Augustine, Jerry; Cheung, Timothy; Gies, Valerie; Boughton, Jennifer; Chen, Maohui; Jakubek, Zygmunt J.; Walker, Steven; Martinez-Rubi, Yadienka; Simard, Benoit; Zou, Shan
Abstract : A novel AFM-based assay was in agreement with traditional cytotoxicity assays and exposed a size-dependent toxicity of boron nitride nanotubes. Abstract : As boron nitride nanotubes (BNNTs) find increased use in numerous applications, potential adverse health effects of BNNT exposure are a growing concern. Current in vitro cytotoxicity studies on BNNTs are inconsistent and even contradictory, likely due to the lack of reference materials, standardized characterization methods and measurement protocols. New approaches, particularly with the potential to reliably relate in vitro to in vivo studies, are critically needed. This work introduces a novel atomic force microscopy (AFM)-based cardiomyocyte assay that reliably assesses the cytotoxicity of a well-characterized boron nitride nanotube reference material, code named BNNT-1. High energy probe sonication was used to modify and control the length of BNNT-1. The polymer polyethylenimine (PEI) was used concurrently with sonication to produce stable, aqueous dispersions of BNNT-1. These dispersions were used to perform a systematic analysis on both the length and height of BNNT-1 via a correlated characterization approach of dynamic light scattering (DLS) and AFM. Cytotoxicity studies using the novel cardiomyocyte AFM model were in agreement with traditional colorimetric cell metabolic assays, both revealing a correlation between tube length and cytotoxicity with longer tubes having higher cytotoxicity. In addition to the size-dependent cytotoxicity, it was found that BNNT-1 exhibits concentration and cell-line dependent cytotoxic effects.